Economic Burden of Colorectal Cancer in Korea - Ju-Young Byun; Seok-Jun Yoon; In-Hwan Oh; Young Ae Kim; Hye-Young Seo; Yo-Han Lee (Korean Society for Preventive Medicine, 2014)
ObjectivesThe incidence and survival rate of colorectal cancer in Korea are increasing because of improved screening, treatment technologies, and lifestyle changes. In this aging population, increases in economic cost result. This study was conducted to estimate the economic burden of colorectal cancer utilizing claims data from the Health Insurance Review and Assessment Service.MethodsEconomic burdens of colorectal cancer were estimated using prevalence data and patients were defined as those who received ambulatory treatment from medical institutions or who had been hospitalized due to colorectal cancer under the International Classification of Disease 10th revision codes from C18-C21. The economic burdens of colorectal cancer were calculated as direct costs and indirect costs.ResultsThe prevalence rate (per 100 000 people) of those who were treated for colorectal cancer during 2010 was 165.48. The economic burdens of colorectal cancer in 2010 were 3 trillion and 100 billion Korean won (KRW), respectively. Direct costs included 1 trillion and 960 billion KRW (62.85%), respectively and indirect costs were 1 trillion and 160 billion (37.15%), respectively.ConclusionsColorectal cancer has a large economic burden. Efforts should be made to reduce the economic burden of the disease through primary and secondary prevention.